2019
DOI: 10.3390/app9224835
|View full text |Cite
|
Sign up to set email alerts
|

Key Technologies and Development Trends of 5G Optical Networks

Abstract: With the development of 5G, 5G optical networks have gradually received increasing attention from scholars. However, most studies have focused on discussing the technical or market aspect. Furthermore, their findings have not provided a panorama of the technologies in the 5G domain, nor have they provided a detailed understanding of the key technologies and development trends. An optical network is an indispensable type of infrastructure for the development of 5G. Therefore, defining key technologies in this d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The value of SEPs in both technological development and business highlights SEP-protected technologies as essential standards and key methodologies in relevant industries. This study differed from past studies-which only adopted the perspective of patents [23]-in that it adopts SEPs, closer to industry standards and industry technology trends, to observe the development of optical networks. In addition, research indicated that companies with SEPs possess considerable market power because they determine the technology standards in the market [24].…”
Section: Network Analyses Of Technologies Licensed With Sepsmentioning
confidence: 87%
“…The value of SEPs in both technological development and business highlights SEP-protected technologies as essential standards and key methodologies in relevant industries. This study differed from past studies-which only adopted the perspective of patents [23]-in that it adopts SEPs, closer to industry standards and industry technology trends, to observe the development of optical networks. In addition, research indicated that companies with SEPs possess considerable market power because they determine the technology standards in the market [24].…”
Section: Network Analyses Of Technologies Licensed With Sepsmentioning
confidence: 87%
“…can be used to explore the technology development of the selected subject, the technology maturity of the industry, the degree of the industrialization, the resistance encountered after entering the subject industry, the main competition opponents, etc. [35,36]. From the patent analysis, the following can be found: (1) the trend of technological development, (2) the dynamics of competitors, (3) the evaluation of investment opportunities, and (4) the basis for research and development management.…”
Section: Patent Analysismentioning
confidence: 99%
“…In this part, the related data are collected first to understand the current development status of energy blockchain technology based on the scope of the topic, the principles, and technologies of the topic. On the basis of the collected information, the technological keywords of the energy blockchain technology are further summarized and classified [36].…”
Section: Patent Analysismentioning
confidence: 99%
“…Leydesdorff et al [29] downloaded more than 10,000 patents under the Patent Cooperation Treaty (PCT), employed IPC co-occurrence networks in 3-and 4-digit code levels, respectively, and confirmed that 4-digit level is a better option which is more informative and effective in the technological make-up. Chang et al [30], [31] carried out this method on the 5G technology patents and forecasted hot R&D themes by referring to the centrality of each IPC. Yoon et al [21] carried out this method on the Electronic Skin technology and traced the evolving trends and technology position in this field.…”
Section: B Patent Analysismentioning
confidence: 99%